1961
DOI: 10.1073/pnas.47.8.1129
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecificity and Firefly Bioluminescence, a Comparison of Natural and Synthetic Luciferins

Abstract: For economy of hypothesis we exclude from consideration the model of double linker strands bridging DNA segments. DNA itself admirably fulfills the requirements of such linkers (such linkers would have to replicate, for instance) and it seems unnecessary to postulate an added complication without experimental justification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 7 publications
1
53
0
Order By: Relevance
“…The L-LH 2 isomer can also be adenylylated, giving rise to L-LH 2 -AMP; however it is not used further in light production (24,27). …”
Section: Firefly Luciferase Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The L-LH 2 isomer can also be adenylylated, giving rise to L-LH 2 -AMP; however it is not used further in light production (24,27). …”
Section: Firefly Luciferase Reactionsmentioning
confidence: 99%
“…For a long time D-LH 2 was regarded as the only isomer capable of producing light (14,27), the L-LH 2 isomer behaving as an inhibitor (46,47,57), although both D-and L-isomer can be adenylylated by luciferase. Through a mechanism analogous to its synthesis the added L-LH 2 would be adenylylated, converted to L-LH 2 -CoA and then racemized and hydrolyzed to D-LH 2 .…”
Section: Firefly Luciferin Biosynthesis and The Stereo-specificity Inmentioning
confidence: 99%
“…L-Luciferin is an enantiomer of D-luciferin and was synthesized in order to identify the chemical structure of natural D-luciferin [25]. In the standard reaction mixtures, L-luciferin is not used in the luminescence reaction [25].…”
Section: Firefly Luciferin = D(-)-luciferin (D-lh 2 )mentioning
confidence: 99%
“…In the standard reaction mixtures, L-luciferin is not used in the luminescence reaction [25]. L-Luciferin is a potent competitive inhibitor of luciferase and the K i value is between 3 and 4 lM [26].…”
Section: Firefly Luciferin = D(-)-luciferin (D-lh 2 )mentioning
confidence: 99%
“…L-Luciferin is not a substrate for the bioluminescence reaction, 15) and Niwa et al 12) suggested that the larva of L. lateralis possesses approximately 1:1 mixture of D-and L-luciferin by an HPLC analysis using a chiral column. In our analysis, the content of luciferin in the larva of L. lateralis measured by HPLC analysis was larger than that by the L-L reaction analysis (although statistically not significant; Table 1).…”
Section: )mentioning
confidence: 99%